(3GdQhV GdCfa hGdeTQY GdQhj aj JaSjQ eG GTJed Ydjg MOjK GdSjQIs - (3YHO GdQMef Hf YHO Gddg GdNfYej GdSgjdj GdCfOdSj, CHh GdbGSe,J (B581 (3g` s ((3eOjfI UfYGA s)
(3ChdgG (B:s
(3hHYO aEfi EfJMjJ ai gPG GdEedGA Edi EjVGM eG hbY ai SjQI QShd Gddg Udi Gddg Ydjg hSde GdJi SHb Edi JCdjagG CHh HcQ eMeO Hf ESMGb GdeWdHi hdNUgG YHO Gdedc Hf gTGe s
(3BNQgG (B:s
(3hbjd (B: (3Hd SejJ efhfkG dbWgG Ohf GdBeGd ef bhdge (B: (3MHd eefhf Ci ebWhY hai GdJfRjd hEf dc dCLQkG ZjQ eefhf s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ GdYfGhjjf hHYV GdcdeGJ HGdMeQI s
(3YdjgG JbjjOGJ YdjgG JedcGJ ZjQ eDQNI s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
Keywords: (3GdJGQjNs